A Meta-Analytic Review of the Effects of High Stress on Eyewitness Memory - Bornstein, Brian H. (2004)
In the past 30 years researchers have examined the impact of heightened stress on the fidelity of eyewitness memory. Meta-analyses were conducted on 27 independent tests of the effects of heightened stress on eyewitness identification of the perpetrator or target person and separately on 36 tests of eyewitness recall of details associated with the crime. There was considerable support for the hypothesis that high levels of stress negatively impact both types of eyewitness memory. Meta-analytic Z-scores, whether unweighted or weighted by sample size, ranged from -5.40 to -6.44 (high stress condition–low stress condition). The overall effect sizes were -.31 for both proportion of correct identifications and accuracy of eyewitness recall. Effect sizes were notably larger for target-present than for target-absent lineups, for eyewitness identification studies than for face recognition studies and for eyewitness studies employing a staged crime than for eyewitness studies employing other means to induce stress